Inércia versus inovação: a produção residencial multifamiliar contemporânea em Belo Horizonte e São Paulo - Grazielle Nunes de Azevedo (2014)
Considering the current context of multi-family production in Brazil perceives the development of a projetual standardization process is already quite widespread. This uniformity implies effects that can be observed in different scales - building and city. Although the choices are within the building, this being an element of the urban landscape, the impact of their production becomes quite evident in the expanded context of the city. The proliferation of vertical buildings that resemble indistinct copies of models reveals a picture of a indistinct landscape also, which could be attributed to any Brazilian metropolis. Established such a finding, initiates the questioning (we'll call the controversies) that directs the desired study and refers to the condition of design inertia linked to contemporary production of multifamily residential buildings in Brazil. The objective of this work is to investigate how to develop this production, having as clipping of a research the cities of Belo Horizonte and Sao Paulo, considering just the architectural standardization process - phenomenon that relates to the conduct of electing models and replicate them massively. In this sense, we must recognize the convergence of actions and interests on the part of multiple actors, who articulately, determine the production of buildings, within the broad and complex universe that is the context of contemporary configuration of Brazilian cities.